2007
DOI: 10.1021/jp071409e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Propane by Monomeric Vanadium Oxide Sites on Silica Support

Abstract: We investigate possible mechanisms of oxidative dehydrogenation of propane using density functional theory. Monomeric vanadium oxide species supported on silica are modeled by vanadyl-substituted silsesquioxane. Similarly to other catalysts with transition metal oxo bonds, the initial C-H bond activation step is hydrogen abstraction by the vanadyl (OdV V ) group yielding a diradical intermediate in which a propyl radical is bound to a HO-V IV site. This is followed by a propyl rebound mechanism yielding alkoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
219
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(239 citation statements)
references
References 47 publications
19
219
0
1
Order By: Relevance
“…4). The statement [7,8] about the rate-determining nature [55] of alkane activation is not inconsistent with this notion if we consider the first intermediate as a rare species limiting the equilibration of all consecutive steps, much in the way as a conventional Langmuir-Hinshelwood reaction may be limited by a pre-equilibrium.…”
Section: Transition Between Odp and Selective Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…4). The statement [7,8] about the rate-determining nature [55] of alkane activation is not inconsistent with this notion if we consider the first intermediate as a rare species limiting the equilibration of all consecutive steps, much in the way as a conventional Langmuir-Hinshelwood reaction may be limited by a pre-equilibrium.…”
Section: Transition Between Odp and Selective Oxidationmentioning
confidence: 99%
“…1, 2 without making any statement about the atomistic nature of the atom transfer which is likely to occur via radicalic [8] activation. It is obvious that we need twice the reaction (2) in order to complete Eq.…”
Section: Size and Functions Of Active Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been also demonstrated for vanadium oxide supported on oxides, a catalyst for selective oxidations. Vanadyl groups, O = V(O-) 3 have been identified as active sites [30], and two different types of cationic clusters have been used for gas phase studies. The V 4 O 10 Á?…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations concerning the use of vanadia-based silica supported catalysts for propene epoxidation have shown that various parameters of the catalysts, including aggregation state and reducibility of vanadium species, acid/base properties, and vanadium content, need to be considered to account for the catalytic behavior noted for the selective oxidation of propene [15,19]. It has been shown that catalysts with high vanadium dispersion show better performance in a number of oxidation reactions such as propane oxydehydrogenation [31], methanol partial oxidation [32], and also in selective propene oxidation [15,19,33]. The presence of an isolated tetrahedral vanadium oxide species is essential as it facilitates the interaction with -N δ− =N δ+ =O species, a mezomeric form of N 2 O, with the formation of mildly electrophilic oxygen forms.…”
Section: Discussionmentioning
confidence: 99%